Management Concerning Economic Exploitation Cases Against Children In Gorontalo City - Iswandi Rahmatillah Dali (Estudiante Law Journal, 2020)
The purpose of this study is to find out and investigate how the review of parents as perpetrators of exploitation in Gorontalo City, namely to find out the countermeasures by P2TP2A in minimizing cases of economic exploitation of children in Gorontalo City. This type of research is empirical research with data collection techniques through interviews. This research was conducted at P2TP2A “LAHILOTE” Gorontalo City. Based on the results of the study, it was concluded that the act of economic exploitation of children was caused by the victim's parents and the child's own will. Economic exploitation of children when accompanied by violence,will result in mental and psychological disturbances. Parents who carry out economic exploitation of children continuously will have a more serious impact, especially on children,n and disturb the community. For this reason, facilitation for underprivileged parents and carrying out economic exploitation of children must be carried out and child victims of exploitation must be rehabilitated and accompanied for mental recovery. Efforts made by P2TP2A “LAHILOTE” Gorontalo City related to the economic exploitation of children, namely facilitating parents so that they do not carry out economic exploitation of children and providing assistance to children who are victims of economic exploitation. Keywords: Exploitation, Economy, Parents, Children